Declaration of nullity of sacred ordination in administrative proceedings - Kiwior, Wiesław (Prawo Kanoniczne, 2021)
The administrative proceeding in the matter of the declaration of the nullity of sacred ordination is currently regulated by Regulae servandae instruction of 16 October 2001 issued by the Congregation for Divine Worship and the Discipline of the Sacraments, which since 1 October 2011 has been applied in accordance with the changes introduced by Pope Benedict XV in the motu proprio Querit semper of 30 August 2011. This instruction replaced the previous Regulae servandae issued on 9 June 1931 by the Congregation for the Discipline of the Sacraments. The whole procedure consists of two stages: the case instruction, conducted by an ordinary authorized by the head of the Administrative Office of the Roman Rota (here the dean of the Roman Rota) and the legal decision of the case (in the competences of the Office). The studied regulations, adjusted to the Canon Law Code of 1983, guarantee protection of the rights of the priest who lodged a claim concerning declaration the nullity of sacred ordination and lead to forming moral certainty by the commissioners and the dean of the Roman Rota while dealing with the case. Efficient case instruction is possible due to the ordinary and instructor eligibility regarding designation of clerks and assistants as well as dispensing with the procedure when it is demanded by a rightful cause. Another factor is the ordinary’s liability to watch over the observance of the law and application of the prescribed norms.